2012
DOI: 10.1182/blood-2011-07-368506
|View full text |Cite
|
Sign up to set email alerts
|

Connexin-43 in the osteogenic BM niche regulates its cellular composition and the bidirectional traffic of hematopoietic stem cells and progenitors

Abstract: Connexin-43 (Cx43), a gap junction protein involved in control of cell proliferation, differentiation and migration, has been suggested to have a role in hematopoiesis. Cx43 is highly expressed in osteoblasts and osteogenic progenitors (OB/P). To elucidate the biologic function of Cx43 in the hematopoietic microenvironment (HM) and its influence in hematopoietic stem cell (HSC) activity, we studied the hematopoietic function in an IntroductionIn the adult bone marrow (BM), the hematopoietic function is suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 46 publications
2
78
0
1
Order By: Relevance
“…Cells were than stained with Differential Wright Giemsa stain, and then, colonies were enumerated based on size and morphology (Gonzalez‐Nieto et al , 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Cells were than stained with Differential Wright Giemsa stain, and then, colonies were enumerated based on size and morphology (Gonzalez‐Nieto et al , 2012). …”
Section: Methodsmentioning
confidence: 99%
“…While one study has shown that BM stromal CXCL12 secretion requires electromechanical coupling by connexin-43 and -45, 24 another study has shown that connexin-43 deficiency increases BM stromal CXCL12 secretion but it compromises HSC homing and hematopoietic recovery upon myeloablation. 25 This is at least partly due to connexin-43-mediated transfer of high, damaging amounts of reactive oxygen species to the BM stroma, which would protect HSCs during stress hematopoiesis. 26 However, we noted that systemic activation of β-adrenergic receptors, e.g.…”
Section: Autonomic Regulation Of Hematopoiesis and Cancermentioning
confidence: 99%
“…The mechanism how osteocyte regulates osteoblast during G-CSF-induced mobilization is still unclear. Given the fact that conditional deletion of connexin-43 led to dysfunction of osteoblasts and mobilization defect by G-CSF [43], it is conceivable that contact communication through gap junction between osteocytes and endosteal niche cells might be involved in the mechanism of niche regulation.…”
Section: Role Of Osteocytes For the Mobilization Of Hscs/hpcsmentioning
confidence: 99%